USIA MENARCHE DENGAN MIOMA UTERI PADA PASIEN MIOMA UTERI DI POLI KANDUNGAN RSUD DR.M.SOEWANDHI SURABAYA - Enung Mardiyana; Aida Novitasari; Hepta Nur Anugrahini (Poltekkes Kemenkes Surabaya, 2016)
One disease feared by women associated with the female reproductive organs was myomauteri (Indarti, 2004). In Indonesia, myoma uterin was found 2,39% -11,7% of all gynecologicalpatients (Prawiroharjo, 2008). It was found that those who menarche at age 10 years / 11 years,at risk of reproductive diseases 10% faster compared to women who begin menstruating at theage of 14 years (Indarti, 2004). This study aims to determine relationship between age ofmenarche with the incidence of myoma uterin in gynecology outpatients of RSUD dr. Moh.Soewandhi Surabaya.This study was Analytical correlations using cross sectional design. The sample in this studywas 28 client myoma uterin. Purposive sampling used in this research. The independent variablewas the age of menarche and the dependent variable was the incidence of myomas. Data collectionwith interviews to the age of menarche and the medical records for the occurrence of uterinemyoma. To determine the relationship between the variables used Fisher's Exact Test, confidencelevel of 95% (α ≤ 0.05). Based Fisher's Exact Test P (0.224) α (0.05), then Ho accepted. Theseresults suggest there was no relationship between the age of menarche with the type of myomauterin. In this study found that age has nothing to do with the type of myoma uteri, it is in becauseof possible types of myomas influence by other factors such as diet, parity, age, and history.Research related factors that influence the type of myoma uteri yet to be developed.